Probing the internal and external micelle structures of differently sized casein micelles from individual cows milk by dynamic light and small-angle X-ray scattering. (August 2017) - Day, L.; Raynes, J.K.; Leis, A.; Liu, L.H.; Williams, R.P.W.
Abstract: Casein micelles vary in size both within and between individual cows depending on the ratios of specific caseins and the level of glycosylation. In this work, milks were obtained from individual cows with known genetic variants of κ- and β-casein, and β-lactoglobulin, containing a range of native micelle diameters. κ- and β-Casein variants are known to influence rennetability of milk. The specific reason for these differences are not known, although, it is clear casein phenotype has an influence. Large and small micelle fractions were also prepared, narrowing the size distribution of micelles at both extremes. When examined by SAXS, all the milk samples were found to have identical scattering patterns in the intermediate and high q regions, implying that the internal structures of casein micelles are the same regardless of their size and genetic variation. When the micelles were exposed to EDTA above 2.7 mM, the inflexion at q ∼0.080 Å −1 in the SAXS curves were diminished indicating changes to internal protein packing due to disruption of the colloidal calcium phosphate nanoclusters within the micelles. Ethanolic buffers caused changes to the micelle diameter, attributed to changes in the micelle internal structure and the collapse of the 'hairy layer' at the micelle surface, evident by the appearance of the inflexion at q ∼0.035 Å −1 and changes in the SAXS curves low q . Despite the large natural variation in micelle size and protein genetic variants, the internal organisation of the micelles is not influenced by diameter or protein genetic variation. Graphical abstract: Highlights: Micelles of a range of native diameters from individual cows and fractions studied by SAXS. The internal organisation of the micelles is not influenced by overall diameter. Ethanol caused changes in micelle internal structure and the collapse of the 'hairy layer'. A dramatic change to SAXS profile at EDTA above 2.7 mM.